Peculiar Features of Thermal Calculation of Oil-Gas Burner for Two-Stage Liquid Fuel Combustion - I. G. Zhykhar (Наука и техника)
The paper reveals peculiar features of thermal calculation of oil-gas burner for two-stage liquid fuel combustion. The dependences for determination of CO, H2, C02 and carbon content in the products of oil gasification have been obtained.